Practical guidance on intensification of insulin therapy with BIAsp 30: a consensus statement - Unnikrishnan, A. G.; Tibaldi, J.; Hadley-Brown, M.; Krentz, A. J.; Ligthelm, R.; Damci, T.; Gumprecht, J.; Gerő, L.; Mu, Y.; Raz, I. (International journal of clinical practice (Esher), 2009)
Summary Background:  Basal insulin and premix insulin are commonly prescribed first‐line insulin therapies for patients failing to maintain glycaemic control on oral therapy. When control on these insulins starts to drift, premix analogues, such as biphasic insulin aspart 30/70 (BIAsp 30), are a simple and effective tool for intensification as they can be injected up to three‐times daily (TID). However, at present, international recommendations for intensification of insulin therapy using premix analogues are limited and specific guidance on dosing is not available for many scenarios. Methods:  In October 2008, an international expert panel met to review the current guidelines for insulin intensification with BIAsp 30 in patients with type 2 diabetes, with the aim of developing practical guidance for general and specialist practitioners. Results:  Simple treatment algorithms have been developed for (i) patients on basal insulin (human or analogue) once daily or twice daily (BID) who need intensification to BIAsp 30 BID, and (ii) patients on BIAsp 30 once daily or BID who can be intensified to BIAsp 30 BID or TID. As well as these algorithms, specific guidance has been provided on dose transfer (from basal insulin to BIAsp 30), dose split (when intensifying from once daily to BID), and combination oral therapies. In addition, a guide to dose titration is included. Conclusions:  The guidelines presented here should enable general or specialist practitioners to use BIAsp 30 to intensify the insulin therapy of patients failing on basal insulin or BIAsp 30 once or twice daily.